Impact of Artificial Intelligence on Consumer Behavior: A Review - Garima Pathania (AG Volumes, 2025)
The business and marketing landscape is undergoing a significant transformation due to the recent advancements in Artificial Intelligence (AI) technology. Since AI is becoming more and more ingrained in consumers’ daily lives, it is critical to comprehend how this relationship will develop in the future. This article discussed how artificial intelligence (AI) is utilised in business, how it affects customer behaviour, how it may be used to analyse consumer behaviour, and what influences consumer behaviour. This article concluded that AI is transforming consumer behavior by enabling personalized recommendations, efficient customer support, and data-driven insights through tools like chatbots, visual search, and voice assistants. It enhances engagement, conversion rates, and brand loyalty while helping businesses predict trends and target consumers effectively. However, ethical data use remains vital. Overall, AI drives smarter, more consumer-centric marketing strategies.